Association between modified weight loss grading system and overall survival in adults with lung cancer: A retrospective cohort study - Cheng, Hao-Qing; Xu, Hong-Xia; Weng, Min; Zhou, Lan; Zhou, Fu-Xiang; Guo, Peng-Xia; Zhang, Ge-Ge; Zhang, Chu-Ying; Shi, Han-Ping; Song, Chun-Hua (JPEN. Journal of parenteral and enteral nutrition, 2025)
This multicenter retrospective cohort study evaluated the prognostic value of the modified weight loss grading system (mWLGS) in patients with lung cancer by analyzing data from 3601 individuals. The investigation demonstrated that mWLGS effectively stratified patient outcomes, with median overall survival progressively declining from 35.5 months for grade 0 to 26.0 months for grade 4. Multivariate Cox regression showed grades 1, 2, 3, and 4 were independently associated with reduced survival, showing incrementally worsening hazard ratios (HR) (HR 1.56, 95% CI: 1.03-2.37, P = 0.037; HR 1.87, 95% CI: 1.24-2.84, P = 0.003; HR 1.94, 95% CI: 1.27-2.96, P = 0.003; HR: 1.95, 95% CI: 1.27-3.00, P = 0.002, respectively). Sensitivity analyses, in which we excluded patients who died within 30 days, showed that mWLGS remained an independent prognostic indicator. The system significantly enhanced prognostic discrimination when combined with TNM staging, as evidenced by improved C-statistics, continuous net reclassification improvement (NRI), and integrated discriminant improvement (IDI). These findings establish that the mWLGS can better stratification the prognosis of patients with lung cancer and is an effective indicator to predict the survival time and quality of life of lung cancer patients.